The Effect Of Concentration Of AB Mix Nutrition And Plant Media On Plant Growth And Results Green Sawis (Brassica rapa) With a System Substrat Hydroponics - Herman Rehatta; Imelda J. Lawalata; Albertina Hiwy (Agrologia, 2023)
The research aimed to examine: 1) The effect of AB Mix nutrient concentration on the growth and yield of green mustard, 2) The effect of growing media on plants mustard greens under a substrate hydroponic system, 3) The interaction effect hydroponic nutrient concentration and growing media (cocopiet, husk charcoal and sand) under the substrate hydroponic system. The study used a two-factor randomized block design with three replications. Observation variables included: plant height, leaf number , leaf area, plant fresh weight, root length and root fresh weight. The results showed that the nutrient concentration treatment of AB Mix showed insignificant effects on the variables of plant height (42 Day After Planting), root length and root fresh weight but gave significant effects on leaf number (42 DAP), leaf area and plant fresh weight. The treatment of growing media and the interaction between nutrient concentrations of hydriponic nutrient and growing media showed insignificant results for all observed variables.